Leerformeln der Raumordnung - Wiek, Klaus-Achim (ERDKUNDE, 1980)
In spatial ordering the open formula is a framework which has been created by the legislature in order to give the executive scope for action. Two open formulas and their fillings are investigated: the one of the larger = more efficient communities (Law for the preparation of territorial reform in the Saarland), and the one concerning Reduction of disparities in the conditions of life (Federal Regional Planning Programme). The geographical examination identifies unsuitable fillings, which arise through non recognition of the results of spatial functions (inter alia in respect of urban quality of life). The example of the territorial reform of the Saarland is used to show that the postulate of concretisation of open formulas is not fufilled by the latter, being ineffectively filled by the substitution of the range of effectiveness by the population total (minimum size of community 8,000 inhabitants). An appeal is made to the public administration not only to call in geographers for assessment of fillings already completed, but to let them participate in the examination of alternative fillings in time before the act of legislation has taken place. In this way a symbiosis of geographical science and regional planning might be achieved.